Effect of MVA Indigenous Isolates and Types of Planting Media on Growth and Result of Corn Plant on Dry Land Central Lombok - Sukmawati Sukmawati; I Made Adnyana; Dewa Ngurah Supraptha; Rizki Busaifi (Postgraduate, University of Mataram, 2022)
The potential of agriculture in Indonesia has not been fully explored. Indonesia has favorable climatic conditions, natural resources and human resources. West Nusa Tenggara (NTB) has an unproductive land area of 1.807.463 ha of the total area of NTB. One of the efforts to increase the productivity of dry land is the application of biological fertilizer. Biofertilizer that are expected to have a high contribution in increasing fertilization efficiency are Vesicular Arbuscular Mycorrhizae (MVA). MVA is important to apply to infertile soils with low nutrient content. The aim of this study was to determine the effect of MVA isolates Indegenous and media types on the growth and yield of corn plant on dry land in Central Lombok The study was carried out for 3 months using a Completely Randomized Design (CRD) with consisted of 2 factors, namely the Indegenous MVA isolate type factor with consisted of 3 levels and the planting media type factor consisting of 4 levels where each treatment was repeated 3 times so that 36 unit were obtained test. The results showed that the variety of isolates showed significant differences in all parameters of growth and yield of corn plat (plant height, root lengthand root weight). The type of planting media showed a significant difference in the parameters of root weight of corn plants. The high growth and yield response of corn plant was thought to be due to the association between corn plant and MVA which was seen in the increased plant growth in all MVA inoculated treatments with the highest plant growth in the treatment using isolate I2 (Gigaspora sp.) on the parameters observed for plant height, root length and root weight. In all parameters observed for cornÂ plant growth, it was found that the genus Gigaspora was superior to the genus Glomus. The best kind of planting media in increasing the growth of corn plants is a mixture of rice husk and soil biochar media with a ratio of 1:3. The use of husk and soil biochar media that was given spores of the genus Gigaspora gave the best corn plant growth